AUDIT SISTEM MANAGEMENT MUTU ISO 9001:2015 DAN SISTEM MANAJEMEN KEAMANAN PANGAN ISO 22000:2018 DI INDUSTRI OLEOKIMIA KAWASAN INDUSTRI MEDAN (KIM) MABAR - Pravil Mistryanto Tambunan; Fariza Habibi; hajatina hajatina (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2021)
ISO 9001:2015 Quality Management System and ISO 22000:2018 Food Safety Management System audit has been carried out in one of the oleochemical industries in the Medan Industrial Estate (KIM) Mabar. The audit is carried out in two stages, first on internal audit and second on visit by external certification body. The internal audit is coordinated by management representatives and carried out by 10 internal auditors whose competencies have been adjusted. The audit results are submitted to management through management review meetings and all agreed corrective actions are closed out by the relevant auditee. This research is a qualitative descriptive study, with the aim of comparing the results of internal audits with audits conducted by external certification bodies to test whether there are repeated findings caused by ineffective corrective actions. The results showed that from the results of the internal audit there were 21 findings related to documentation, policies, operational control, pest control, HACCP, and others. Meanwhile, the external audit only found problems with supplier control. The internal audit that has been carried out has proven to be effective so that the problems found internally are not repeated in the external audit, but it is necessary to strengthen the internal audit side related to supplier control.